Students' Academic Procrastination in Learning Scientific Writing: Conditions, Prevalence, and Classifications - Cahyono, Bambang Eko Hari; Asri, Dahlia Novarianing (Journal of Educational Science and Technology (EST), 2024)
The purpose of this study was to describe the conditions of learning Scientific Writing, the prevalence and classifications of academic procrastination among students in this context. This study uses quantitative and qualitative descriptive approaches. The subjects of the study were students of the Indonesian Language and Literature Education Study Program, Universitas PGRI Madiun, who were taking the Scientific Writing course.Scales for academic procrastination, observation manuals, and document grids were the tools utilized to collect data. Data collection techniques were carried out through psychological assessments, passive participant observation, and document studies. While qualitative data analysis makes use of an interactive analytical model, quantitative data analysis makes use of descriptive statistics. The results of the study show that learning to write scientific papers has not been implemented properly. In addition, it is also known that there are several weaknesses in scientific works written by students, namely in the aspects of arranging logical thinking, discussion sequence, data literacy, argumentation, references, sentence and paragraph arrangement, use of spelling, scientific writing style, and originality. The level of academic procrastination among students in the Scientific Writing learning is relatively high. Compared to female students, men students put off learning Scientific Writing more often. The level of academic procrastination is correlated with student learning achievement.